Urinary proteins, vitamin D and genetic polymorphisms as risk factors for febrile urinary tract infection and relation with bacteremia: a case control study. - Willize E van der Starre (PLoS ONE, 2015)
Objective/purpose Febrile urinary tract infection (UTI) is a common bacterial disease that may lead to substantial morbidity and mortality especially among the elderly. Little is known about biomarkers that predict a complicated course. Our aim was to determine the role of certain urinary cytokines or antimicrobial proteins, plasma vitamin D level, and genetic variation in host defense of febrile UTI and its relation with bacteremia. Methods A case-control study. Out of a cohort of consecutive adults with febrile UTI (n = 787) included in a multi-center observational cohort study, 46 cases with bacteremic E.coli UTI and 45 cases with non-bacteremic E.coli UTI were randomly selected and compared to 46 controls. Urinary IL-6, IL-8, LL37, β-defensin 2 and uromodulin as well as plasma 25-hydroxyvitamin D were measured. In 440 controls and 707 UTI patients polymorphisms were genotyped in the genes CXCR1, DEFA4, DEFB1, IL6, IL8, MYD88, UMOD, TIRAP, TLR1, TLR2, TLR5 and TNF. Results IL-6, IL-8, and LL37 are different between controls and UTI patients, although these proteins do not distinguish between patients with and without bacteremia. While uromodulin did not differ between groups, inability to produce uromodulin is more common in patients with bacteremia. Most participants in the study, including the controls, had insufficient vitamin D and, at least in winter, UTI patients have lower vitamin D than controls. Associations were found between the CC genotype of IL6 SNP rs1800795 and occurrence of bacteremia and between TLR5 SNP rs5744168 and protection from UTI. The rare GG genotype of IL6 SNP rs1800795 was associated with higher β-defensin 2 production. Conclusion Although no biomarker was able to distinguish between UTI with or without bacteremia, two risk factors for bacteremia were identified. These were inability to produce uromodulin and an IL6 rs1800795 genotype.